Building fresh product supply chain cooperation in a typical wholesale market. Issue 5 (1st May 2017) - Hou, Xiangyu; Liu, Dacheng
Abstract: In China, the fresh product supply chain is usually connected by a wholesale market. This feature, as well as the product's perishability, has a great influence on the chain. The market price is exogenous and stochastic because it is actually determined by the uncontrollable supply and demand in the market. The wholesaler reacts to the stochastic price, and based on his experience, he may refuse to sell and may retain fresh products with relatively long lifetime when the price is low. When purchasing at the market, the retailer is incapable of distinguishing the quality change during the delay caused by the wholesaler. However, the difference in quality becomes obvious with faster deterioration in the retail store, and the retailer's sales are influenced accordingly. The ' market ' works well in pricing the products and matching supply and demand, but it cannot prevent the wholesaler delaying the sales due to the retailer's incapability. We explain this situation as a result of quality information asymmetry and fix it by coordinating the supply chain; we expect a cooperation mechanism in which the wholesaler cannot improve his profit by delaying the sales even when he has access to the market. The wholesaler's behavior under market price uncertainty is simplified and described. With the wholesaler's behavior taken into account, the average quality distribution in the market is approximately estimated. With the approximated description, we construct the model and design the mechanism to coordinate the wholesaler and retailer. A numerical experiment based on an actual market situation is developed and analyzed; the reason why most existing contracts fail is discussed, and managerial suggestions are provided for the practitioners.